2020
DOI: 10.3389/fonc.2020.571304
|View full text |Cite
|
Sign up to set email alerts
|

Combination Treatment With Paclitaxel, Carboplatin, and Cetuximab (PCE) as First-Line Treatment in Patients With Recurrent and/or Metastatic Nasopharyngeal Carcinoma

Abstract: Background: Platinum-containing doublet chemotherapy regimens are generally considered the standard first-line systemic therapy for recurrent or metastatic (R/M) nasopharyngeal cancer (NPC). Gemcitabine (GEM) plus cisplatin (CDDP) has become a standard therapy based on a phase 3 study in several countries, yet this regimen sometimes affects quality of life due to nausea or appetite loss. Here, we present the manageable toxicity and promising activity of paclitaxel + carboplatin + cetuximab (PCE) therapy for R/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Given the frequency of epidermal growth factor receptor (EGFR) expression on NPC, in 73.3-84.1% of cases ( 17 20 ), several studies evaluated treatment with anti-EGFR therapy in collaboration with CRT for LA-NPC ( 21 23 ) and with chemotherapy for R/M NPC ( 15 , 24 26 ), and reported promising clinical efficacy against these diseases. As an example of the former, Hao et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the frequency of epidermal growth factor receptor (EGFR) expression on NPC, in 73.3-84.1% of cases ( 17 20 ), several studies evaluated treatment with anti-EGFR therapy in collaboration with CRT for LA-NPC ( 21 23 ) and with chemotherapy for R/M NPC ( 15 , 24 26 ), and reported promising clinical efficacy against these diseases. As an example of the former, Hao et al.…”
Section: Discussionmentioning
confidence: 99%
“…These suggest that Cmab-containing regimens may be worth testing in anticipation of an improved prognosis. Indeed, we recently reported that the PCE regimen was effective even in patients with R/M NPC (n=14), among whom 92% of evaluable patients experienced tumor shrinkage, with ORR and CR rates of 58.3% and 16.7%, respectively ( 15 ). However, no study has evaluated IC-PCE in the treatment of LA-NPC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In R/M NPC patients, the clinical trial demonstrated that Paclitaxel Carboplatin plus Cetuximab (PCE) could achieve a 58.3% ORR rate, with better efficacy and acceptable side effects. It is worth mentioning that patients can receive this treatment on an outpatient basis [ 99 ]. The combination of CTX has become one of the first-line treatment options for patients with advanced nasopharyngeal carcinoma.…”
Section: The Role Of Egfr Targeting In Nasopharyngeal Carcinomamentioning
confidence: 99%
“…In a number of centers, Ueda and colleagues [82] investigating a combination treatment of carboplatin, paclitaxel and cetuximab in patients with metastatic or recurrent or with repeated platinum-resistant NPC showed good survival benefit, an overall response rate reach to 64 % and a median OS of 29.1 months with follow up for 30 months. The treatment with gefitinib had little response rates in metastatic and recurrent NPC treated previously with platinum-based chemotherapy.…”
Section: Novel Therapies: Molecular-targeted Agentsmentioning
confidence: 99%